Industrialization and Urban Development in Kaduna Metropolis, 1957-1986 - Benjamin Oladokun (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
The purpose of this study is to examine Industrialization and Urban Development in Kaduna metropolis, 1957-1986. This is important because the connection between Urbanization and Industrialization are key instruments in the rapid transformation of most cities and urban centres. In the study we attempted to examine the Theoretical Foundation of Industrialization. We argue that the concept of ‘manufacturing’ and ‘industry’ are not synonymous to each other. We also discussed factors that influenced the choice of Kaduna as a centre for the establishment of industries. These include availability of water, raw materials, strategic/ geographical location, and role of government. And, lastly, we showed how the large-scale manufacturing factories in Kaduna have impacted on the development of the metropolis. The impacts are demonstrated in the following ways: Migration, Urban Development, Spatial Pattern, Class formation and Proletarization and its impact on the surrounding hinterland. It starts in 1957, with the establishment of the Kaduna Textiles Limited, which was the first large scale manufacturing industry in the city.1 The study terminates in 1986, with the introduction of the Structural Adjustment Programme (S.A.P.) in the nation’s economy, with its devastating effects on the industrialization process in the country. Through historical methodology, the paper demonstrates ways in which the manufacturing industry contributed to the development of Kaduna metropolis. Hence, the city grew from a military garrison and administrative town, into an industrial city, which was commonly known as the ‘Manchester of Nigeria’.